The processing and analysis of graphene and the strength enhancement effect of graphene-based filler materials: A review. (December 2020) - Shen, C.; Oyadiji, S. Olutunde
Abstract: Research on graphene, a single-atom thick material, has been an intensive research area since the end of the 20th century, especially after the discoverers of graphene were awarded the Nobel prize in 2010. The material has attracted much interest and in the past decade the development of graphene can only be described as outstanding. Tens of thousands of papers relevant to the application of graphene have been published. Graphene has good physical properties including strength, electrical conductivity and thermal conductivity. It also has stable chemical properties. Among all of the outstanding properties of graphene, its mechanical properties are one of the best. Ideally its Young's modulus can reach 1 TPa and its tensile strength can reach 130 GPa. These theoretical values are higher than those of all metals and are the highest values among all materials discovered so far. The potential applications of graphene products have even exceeded those of silicon material. For some time, this has led to a greater research activity on graphene than on silicon. Currently the research on graphene is mainly focused on medical equipment, composites, conductive materials and super capacitors. This review will introduce the processing and analysis of graphene and the application of graphene in the material strength enhancement field. The application of graphene family material in this area will be introduced along with its processes. At this moment, the application of graphene in material enhancement is limited by the lack of large volume of graphene and cost. Graphene and graphene-based materials can enhance material strength to some extent, but it is not yet cost-effective enough. Currently, the application of graphene and graphene-based materials for strength enhancement is more realistic in the military and aerospace sectors. Graphical abstract: This review is about the application of graphene family materials in material strength enhancement field. Apart from detailed mechanical data of graphene enhanced materials, the background information, manufacture, classification and processing methods of graphene family materials are introduced. This article is suitable for beginners doing research in graphene to acquire necessary knowledge of graphene and the approach to enhance the mechanical strength of common materials. Image 1 Highlights: Classification of graphene fabrication methods. Differences in mechanical properties of graphene at micro and macro levels. Differences in morphological and physical properties of graphene family material. Comparison of mechanical properties for graphene enhanced material.